A Probabilistic Approach to Fiscal Space and Prudent Debt Level : Application to Low-Income Developing Countries - Adedeji, Olumuyiwa (IMF Working Papers; Working Paper ;, 2016)
What constitutes fiscal space or a prudent level of debt to conduct countercyclical policy while ensuring debt sustainability? This paper addresses the question by exploring the relationship between debt dynamics, and the probabilistic distribution of the primary balance and the effective interest rate. This proposed approach is useful in situations where the lack of relevant data makes it difficult to estimate detailed fiscal reaction functions. Applying this approach to Low-Income Developing Countries (LIDCs) and based on various debt ceiling assumptions, we find that about 60 percent of these countries presently have fiscal policy space to address adverse shocks, subject to the availability of domestic and external financing. Countries with strong institutional capacity tend to have more fiscal space, and countries with weak institutional capacity, mostly countries in conflict and fragile states, tend to lack fiscal space.